An open label randomized clinical trial comparing the safety and effectiveness of one, two or three weekly pentamidine isethionate doses (seven milligrams per kilogram) in the treatment of cutaneous leishmaniasis in the Amazon Region. - Ellen Priscilla Nunes Gadelha; Rajendranath Ramasawmy; Bruna da Costa Oliveira; Nágila Morais Rocha; Jorge Augusto de Oliveira Guerra; George Allan Villa Rouco da Silva; Tirza Gabrielle Ramos de Mesquita; Carolina Chrusciak Talhari Cortez; Anette Chrusciak Talhari (Public Library of Science (PLoS), 2018)
BACKGROUND:American Cutaneous Leishmaniasis (ACL), a vector borne disease, is caused by various species of Leishmania and in the Amazonas, Leishmania guyanensis is predominant. The recommended drugs for treatment of cutaneous leishmaniasis (CL) in Brazil are pentavalent antimonials, pentamidine isethionate (PI) and amphotericin B. Pentamidine was initially used as metanolsulfonate or mesylate (Lomidine) at a dose of 4 mg/kg/daily, containing 2.3mg of base. This drug was withdrawn from the market in the eighties, and currently is available as PI. The PI dose required to achieve an equivalent dose of pentamidine base is 7 mg/kg, rather than the 4 mg/kg that is currently recommended in Brazil. OBJECTIVES:The aim of this study was to evaluate the efficacy and safety of PI in a single dose, two or three doses of 7 mg/kg body weight, intramuscularly, with an interval of seven days between each dose. MATERIALS AND METHODS:This study was conducted as a controlled, randomized, open-label clinical trial for a total number of 159 patients with CL. Individuals aged 16-64 years with one to six lesions of confirmed CL based on amastigotes visualization in direct examination of Giemsa stained of dermal scraping from the border of the lesion with no previous treatment for CL and no abnormal values for liver enzymes were eligible to participate in the study. Patients with history of diabetes, cardiac, renal, and hepatic disease as well as pregnant women were excluded. Cure was defined as complete healing in the diameters of the ulcers and lesions skin six months after the end of the treatment. RESULTS:From November 2013 to December 2015, 159 patients were screened and allocated in three groups for treatment with PI: i) 53 patients were treated with a single dose intramuscularly injection of 7 mg/kg body weight; ii) 53 received two doses of 7 mg/kg within an interval of seven days; and iii) 53 were treated with three doses of 7mg/kg with an interval of seven days between each dose. In 120 patients, L. guyanensis was identified. A cure rate of 45%, 81.1% and 96.2% were observed in the first, second and third group, respectively. The cure in the three PI dose group was higher compared to the single-dose (p<0.0001) and two-dose groups (p = 0.03). No serious adverse events occurred. CONCLUSION:The present study shows that PI is a safe drug and its efficacy varied with the number of doses. The administration of PI in patients with ACL, predominantly caused by L. guyanensis, was mostly efficient in three or two doses of 7 mg/kg. TRIAL REGISTRATION:ClinicalTrials.gov NCT02919605.